ARTERIAL HYPERTENSION IN PATIENTS WITH BRONCHIAL ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - N. A. Karoli; A. P. Rebrov (Klinicist)
Aim – to study the frequency of occurrence and characteristics of arterial hypertension (AH) in patients with bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD).Materials and methods. The study included 390 asthmatic patients (130 men and 260 women) and 230 patients with COPD (226 men and 4 women).Results. Hypertension was detected in 158 (40.5 %) asthmatic patients and in 142 (61.7 %) patients with COPD. Analysis results give evidence of higher detection rate of hypertension, as well as higher average systolic and diastolic blood pressure in different age groups in patients with chronic obstructive pulmonary disease, compared with data in the population. This suggests that presence of chronic obstructive pulmonary disease is a risk factor for hypertension in the population.Conclusion. Unlike in patients with essential hypertension, patients with chronic obstructive pulmonary disease and arterial hypertension family history is not typical. Risk factors for hypertension in patients with asthma were: female sex, severity of disease, overweight. In men with COPD risk factors of hypertension included overweight, reduced forced expiratory volume in first second < 50 % of predicted.